PRODUKTIVITAS FI’IL DALAM PERUBAHAN DAN PEMAKNAAN (ANALISIS MORFOSEMANTIK TERHADAP KAMUS ARAB-INDONESIA KARYA MAHMUD YUNUS) - Ashief El Qorny (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2017)
Arabic is one of the main languages in the world and rich with cultural heritage. Arabic has a strong influence in literature and even in media. According to Ulama or Scholars, Arabic language is the most proper language which can explains a wider meaning with lafaz or simple word. The formation of a word can refer to several meanings. The Arabic vocabulary covers all fields. In its development, the Arabic language has borrowed many vocabularies from other languages, however, Arabic has also contributed a great deal to Eastern and Western languages. This can be found on the words which are in the Arabic dictionary. Theory of language that became the foundation of this research can help the writer in choosing the right concept to analyze the object of this research. Moreover, in this research, the writer will use a morph semantics concept which combines morphological and semantic concept. Morph semantic can be interpreted as a branch of linguistics that identifies grammatical units and their meanings. This research uses descriptive-analytical method, a research method that try to describe and interpret object with what it is. The study uses a qualitative approach, namely analytical procedures that produce descriptive data in the form of words written or spoken of the person or behavior that can be observed. The resultof this study indicates that; (1) Fi'l ma>di> in the dictionary does not undergo all changes according to the existing rhymes, only a few can experience the form of the fi'l ma>di> to mazi>d. (2) Productivity meaning fi'l mazi>d in Arabic-Indonesian dictionary on wazan فعّل is التعدية, on wazan فاعلisقد يكون بمعنى فَعَلَ المجرد, on wazan أفعل is التعدية, on wazan تفعّل is للتكليف and الصيرورة, on wazan تفاعل is للمشاركة, on wazan انفعل isلمطاوعة فَعَلَ , on wazan افتعلis لمطاوعة فَعَلَ, on wazan افعلّ is الدلالة على الدخول في الصفة, on wazan استفعل is للطلب , on wazan افعوعل is قد يكون بمعنى المجرد.",